The Role of Affect Management for HIV Risk Reduction for Youth in Alternative Schools - Brown, Larry K. (J Am Acad Child Adolesc Psychiatry, 2017)
OBJECTIVE: Adolescents in alternative schools for behavioral and emotional problems have an earlier sexual onset and higher rates of sexual risk than their peers. They also often have difficulty managing strong emotions, which can impair sexual decision-making. Human immunodeficiency virus (HIV) prevention programs for these adolescents may be most effective if skills for coping with strong emotions during sexual situations are included. METHOD: This paper reports the 6-month outcomes of a three-arm randomized controlled trial comparing an HIV prevention intervention with affect management (AM) to a standard, skills-based HIV prevention intervention (SB), and a general health promotion intervention (HP). HP was similar to a general health class, and SB was based on previous effective HIV prevention programs used with community adolescents, while AM included affect management skills in addition to effective HIV prevention skills. Youth (n=377) in two US cities were ages 13 to 19 and attending alternative schools for behavioral and emotional problems. RESULTS: Multiple logistic regression analyses, adjusted for the baseline scores, age, and gender, found adolescents in AM were significantly less likely to report being sexually active at follow-up (80% vs. 91%, adjusted odds ratio [AOR] =0.28, CI=0.08–0.96) and more consistently using condoms than those in HP at follow-up (62%, vs. 39%, AOR=3.42, CI=1.10–10.63). CONCLUSION: Affect management techniques tested in this project, focused on sexual situations, are similar to those that are used in dialectical behavioral therapy (DBT) and in clinical practice. These data suggest that these techniques might decrease risk behaviors and improve the health of adolescents with emotional/behavioral problems.